CLASSICAL DEFINITION OF PROBABILITY: THEORETICAL FOUNDATIONS AND PRACTICAL APPLICATIONS - Shingis Maykhanovich Urmanov (European Science Publishing, 2024)
The classical definition of probability is one of the basic concepts in probability theory. This article explores the theoretical foundations of the classical definition of probability, its formulation and application, as well as its role in modern statistics and probability models. The article is intended for students and researchers in the field of mathematics and statistics.
Keywords: probability, measure, degree, confidence, event, theory.